Identification of critical P level for sunflower (Helianthus annuus L.) in solution culture for P acquisition: IDENTIFICATION OF CRITICAL P LEVEL FOR SUNFLOWER IN SOLUTION CULTURE FOR P ACQUISITION - A AZIZ QURESHI; LAKSHMI PRAYAGA (Journal of Oilseeds Research, 2016)
Solution culture experiment was conducted during November 2012 at ICAR-Indian Institute of Oilseeds Research, Hyderabad with a protocol to identify the critical level of phosphorus (P) in nutrient solution suitable to produce initial growth of sunflower that could be able to distinguish the deficiency effect from sufficient level. The study showed that 2.0ppmP was found to be critical in solution to arrest the normal growth ofshoot, root, dry matter and P uptake at 30 days of sowing. The regression coefficient obtained between total dry matter and P levels in solution culture was found be to highly significant (R2=0.97). The best fit curve through quadratic equation was found to be Y= -0.0496x2+0.713x +0.5932. The results obtained in this studywould provide the basis for conducting rapid screening ofsunflower genotypes for P acquisition and identification of distinct changes in root modifications against P stress or starvation during the initial plant growth period (up to 30-45 days).